Stamp duty relief and anti-avoidance provisions - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2018)
Reliefs from stamp dutyIn certain circumstances, stamp duty reliefs may be applicable to instruments that would otherwise be dutia-ble, provided that the reliefs are claimed within specified statutory time limits. Such reliefs are distinct from stamp duty remissions, which may be granted by the Minister through the exercise of his powers under Sec-tion 74 of the Stamp Duties Act (Cap 312, 2006 Ed.). Under Section 74 of the Stamp Duties Act, the Minister has the discretion to prospectively or retrospectively reduce or remit duties subject to such conditions as he may impose. This power may be exercised on a general basis or on a case-by-case basis. When exercised on a general basis, the Minister will provide for subsidiary legislation in the form of rules and shall specify the conditions (if any) in the rules.